Orthopedic Surgeries: Review of Physicological Effect Pre and Post-Surgical Treatments - Satria Putra Wicaksana (HM Publisher, 2021)
Patient satisfaction with treatment is an important outcome measure and is associated with increased adherence to that treatment. The role of psychological factors with regard to successful surgical outcomes has been highlighted previously. This is orthopedic literature for the psychological traits that are relevant to surgical outcomes as well as an overview of options for psychologically optimizing a patient for surgery and ways to address problems encountered in the postoperative period in pandemic or non-pandemic before. A literature review was conducted in the electronic database PubMed using the keywords “Psychological”, and “Orthopedic Surgeries”. All type of studies were included for this study, such as controlled trials, systematic reviews, literature reviews, and pilot studies published between 2015 and 2021. Articles which not written in English were excluded from the study. This search resulted in 6 papers. All of the papers discuss the physicological effect on pre and post-surgical treatment. Satisfaction with surgery was closely associated with physical function and anxiety before surgery. Our analysis provides low levels of evidence supporting the use of psychological interventions, particularly with regard to anxiety and mental components of quality of life. Pre-operative anxiety, depression and low self-efﬁcacy are consistently associated with worse physiological surgical outcomes and quality of life. However, there is currently insufﬁcient evidence to be sure that pre-operative psychological interventions are of beneﬁt, or which interventions are most effective.